2009
DOI: 10.1590/s1516-89132009000200026
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil yield and composition of Lamiaceae species growing in southern Brazil

Abstract: The Lamiaceae family has been described to be rich in essential oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
(19 reference statements)
0
22
0
1
Order By: Relevance
“…Those EOs were characterized by a medium/high amount of eucalyptol (18-14%), menthofuran (15-17%), and caryopyllene (12-16%). Agostini et al [26] studied the chemical characterization of EO extracted from M. aquatica collected in Brazil and reported that the EO chemical composition was dominated by menthofuran (53%), with a number of other minor compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Those EOs were characterized by a medium/high amount of eucalyptol (18-14%), menthofuran (15-17%), and caryopyllene (12-16%). Agostini et al [26] studied the chemical characterization of EO extracted from M. aquatica collected in Brazil and reported that the EO chemical composition was dominated by menthofuran (53%), with a number of other minor compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils were extracted by hydrodistillation method from the dried plant leaves for 1 h in a Clevenger-type apparatus according to Agostini et al (2009) …”
Section: Essential Oil Extraction and Chemical Identificationmentioning
confidence: 99%
“…In the The composition of essential oil of in the present study is different from those reported in recent studies. [2,10] The identical Botanical plant in fact can give more or less important different extracts, biochemical specificity and proprieties of some plants are varied in different regions. [11] In present study, results are compared with other previous studies and examined the similarities and the differences of this plant in different regions and with other species that belong to the same genus.…”
Section: Chemical Compositionmentioning
confidence: 99%